INTERNAL AND EXTERNAL FACTORS RELATED TO THE IMPLEMENTATION OF PATIENT SAFETY GOALS: A LITERATURE REVIEW - Astarini, Made Indra Ayu; Lilyana, Maria Theresia Arie (Universitas Nahdlatul Ulama Surabaya, 2021)
Background: Patient safety goals are important things that must be done by nurses to get a patient safety culture. Individual internal factors and external factors can influence nurses in carrying out patient safety goals. Objective: This literature review study aims to discuss further internal and external factors that correlated in implementing patient safety goals by nurses. Methods: The design used was literature review. The keywords are in two languages. The keywords for articles in Indonesian are “faktor yang mempengaruhi”, “sasaran keselamatan pasien”, “perawat”, “rumah sakit”. The keywords for English articles are